Analisis Korelasi Kepatuhan Hukum K3 Terhadap Produktivitas SDM Melalui Data Kecelakaan Kerja Nasional Portal Satu Data - Mardiman, Mardiman; Taufik, Taufik; Bagaskoro, M Rizal; Rasiwan, Iwan (Jurnal Indragiri Penelitian Multidisiplin, 2026)
This study analyzes the correlation between Occupational Safety and Health (OSH) legal compliance and Human Resource (HR) productivity using national workplace accident data from Indonesia's Single Labor Data Portal (2019-2024). A qualitative approach with documentary study design and thematic analysis was employed to identify relational patterns and causal mechanisms, using accident rates as a proxy for OSH compliance. Findings reveal a 152.7% surge in accident cases (from 182,835 to 462,241), indicating systemic enforcement deficiencies. Three causal pathways were identified: (1) reduced workforce capacity due to absenteeism (14-28 days recovery) and permanent disability (6.17% fatality rate); (2) 32% higher motivation and job satisfaction in companies with structured OSH systems; and (3) resource reallocation from accident cost savings (IDR 5-500 million/case) toward HR competency development. Results refute the assumption that OSH is a financial burden, confirming instead that safety investment is a prerequisite for sustainable productivity. Sectoral disparities (construction 29-32%, manufacturing 26%) and severe underreporting (94% in peripheral regions) reflect regulatory gaps, enforcement deficits, and cultural barriers. Policy recommendations include risk-based regulatory reform, digital supervision systems, and OSH integration into vocational curricula to transform compliance from procedural obligation into a strategic productivity driver. The study contributes empirical evidence linking legal compliance with tangible productivity outcomes in Indonesia's labor context.